2016
DOI: 10.1037/sgd0000192
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as a coping strategy for bias-based school victimization among Latina/o sexual minority youth.

Abstract: This study examined whether mindfulness strategies (e.g., acting non-judgmentally with awareness and attention to present events) were effective in mitigating the associations among school-based victimization related to ethnicity and sexual orientation, well-being (i.e., depressive symptoms and self-esteem), and grade-point average (GPA). The U.S.-based sample included 236 Latina/o sexual minority students, ranging in age from 14 to 24 years (47% were enrolled in secondary schools, 53% in postsecondary schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 65 publications
(102 reference statements)
1
25
0
Order By: Relevance
“…That is, associations between sexual orientation-based coping and depressive symptoms and self-esteem were only significant for those with low levels of mindfulness. 37 Another study exploring the relationship between mindful attention, self-esteem, and psychological QoL in lesbian, gay, bisexual, and transgender participants (n=177) found that mindful attention and self-esteem moderated the relationship between perceived stress and psychological QoL. Specifically, although mindful acceptance buffered the relationship between stress and psychological QoL at low-to-moderate levels of stress, it did not have an impact at higher levels of stress.…”
Section: Resultsmentioning
confidence: 99%
“…That is, associations between sexual orientation-based coping and depressive symptoms and self-esteem were only significant for those with low levels of mindfulness. 37 Another study exploring the relationship between mindful attention, self-esteem, and psychological QoL in lesbian, gay, bisexual, and transgender participants (n=177) found that mindful attention and self-esteem moderated the relationship between perceived stress and psychological QoL. Specifically, although mindful acceptance buffered the relationship between stress and psychological QoL at low-to-moderate levels of stress, it did not have an impact at higher levels of stress.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that while some aspects of someone's identity and culture confer risk in one domain, they may also confer resilience in another domain of an individuals’ life—a complexity that emerges at the interface of ethnic identity and sexual identity, rather than as an additive function of the two. These findings warrant further analysis to understand how coping with discrimination (e.g., Kuper, Coleman, Mustanski, 2014; Toomey & Anhalt, ) and internalized homonegativity intersect and shape each other, as both have been shown to differ across migration and generational status (Morales, ), to impact neurobiological regulation of individuals who belong to multiple marginalized social groups.…”
Section: Intersectionality As a Framework To Examine Neurobiological mentioning
confidence: 99%
“…Higher levels of mindfulness protected against the effect of victimization due to sexual orientation but not due to ethnicity on depressive symptoms in the past week among young Latino sexual minority youth in the US ( 28 ). Mindfulness has also been shown to protect against other stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Two population-based studies in Europe found that mindfulness scores for select facets differ by sex, age, education, and income ( 24 , 25 ), but there have been no comparisons by sexual orientation to date. Only two recent studies have published mindfulness data on sexual minorities: a national online convenience sample of gay men aged 40 years and over in Australia ( 26 , 27 ) and a national online convenience sample of Latino sexual minority youth aged 14–24 years in the US ( 28 ).…”
Section: Introductionmentioning
confidence: 99%